Thyroid Dysfunction and Oral Lichen Planus: Evidence From Two-Sample Mendelian Randomization Analysis - Pengxian Xie; Wei Peng (International Dental Journal)
Introduction and aims: Epidemiological studies have shown that the association between thyroid dysfunction (TD) and oral lichen planus (OLP) is controversial, and the causal relationship remains ill-defined. This study aims to investigate their probable mutual causality using bidirectional Mendelian randomization (MR) analyses. Methods: We extracted genetic instruments for OLP and 10 phenotypes of TD from the genome-wide association studies database. The inverse variance weighted method was primarily used to evaluate the bidirectional causal relationship between TD and OLP. The results’ robustness was verified by sensitivity analysis (Cochran's Q test, MR-Egger intercept, and leave-one-out test). Bonferroni correction threshold (0.05/10) was applied to determine significant differences. Results: Forward MR analysis indicated that Hashimoto's thyroiditis (HT) was suggestively linked to a higher likelihood of developing OLP (P = .0077), while hypothyroidism significantly increased the risk of OLP occurrence (P = .0002). The reverse MR study found that OLP was suggestively related to the occurrence of hyperthyroidism (P = .0126) and thyroid cancer (P = .0244). Furthermore, OLP was found to significantly increase the risk of HT (P = 3.47 × 10–⁸), Graves’ disease (P = 1.03 × 10–⁵), hypothyroidism (P = 1.08 × 10–⁸), and elevated thyroid-stimulating hormone levels (P = 1.99 × 10–⁶). No major pleiotropy or heterogeneity was detected (P > .05). Conclusion: These findings suggest that hypothyroidism significantly increases the risk of OLP, while OLP may contribute to the development of autoimmune thyroid disorders, particularly HT, Graves’ disease, hypothyroidism, and thyroid-stimulating hormone. These findings highlight the complex interaction between endocrine and immune systems, emphasizing the need for further research into shared molecular pathways and potential clinical implications. Clinical Relevance: This study provides a genetic foundation for understanding the relationship between TD and OLP, which aids early screening and diagnosis and informs therapy development.